Receiving Teachers' Concerns, Stressors, and Resiliency in Handling Learners with Special Needs - Rayvin D. Pestano; Jovelyn V. Pestano; Muhammad Ikhlas; Kuswanto (International Journal of Educational Practice and Policy, 2026)
This study explored the concerns, stressors, resilience, and performance of receiving teachers working with learners with special educational needs (LSEN’s). Utilizing descriptive research design, it surveyed 294 elementary and secondary receiving teachers, using adapted versions of the Teachers Stress Inventory Scale, Concerns on Inclusive Education Scale, and Teachers Resilience Scale. Descriptive statistics alongside Pearson correlation analysis were used to examine the relationships between teachers' concerns, stressors, resilience, and their performance in handling LSEN’s. Results indicated a significant correlation between these factors, highlighting the impact of teachers' concerns, stressors, and resilience on their performance. The study recommends embedding special education content across pre-service teacher education programs and developing resilience-building initiatives to address concerns and stressors, equipping receiving teachers with the essential skills, knowledge, and strategies needed to effectively manage LSEN’s.